BMI, Alcohol Consumption and Gut Microbiome Species Richness Are Related to Structural and Functional Neurological Abnormalities - Geisler, Corinna; Pankoke, Jil; Schlicht, Kristina; Knappe, Carina; Rohmann, Nathalie; Hartmann, Katharina; Settgast, Ute; Türk, Kathrin; Seoudy, Anna Katharina; Franke, Andre; Schreiber, Stefan; Schulte, Dominik M.; et al. (Nutrients, 2021)
Background: The incidence of neurological diseases is increasing throughout the world. The aim of the present study was to identify nutrition and microbiome factors related to structural and functional neurological abnormalities to optimize future preventive strategies. Methods: Two hundred thirty-eight patients suffering from (1) structural (neurodegeneration) or (2) functional (epilepsy) neurological abnormalities or (3) chronic pain (migraine) and 612 healthy control subjects were analyzed by validated 12-month food frequency questionnaire (FFQ) and 16S rRNA microbiome sequencing (from stool samples). A binomial logistic regression model was applied for risk calculation and functional pathway analysis to show which functional pathway could discriminate cases and healthy controls. Results: Detailed analysis of more than 60 macro- and micronutrients revealed no distinct significant difference between cases and controls, whereas BMI, insulin resistance and metabolic inflammation in addition to alcohol consumption were major drivers of an overall neurological disease risk. The gut microbiome analysis showed decreased alpha diversity (Shannon index: p = 9.1× 10−7) and species richness (p = 1.2 × 10−8) in the case group as well as significant differences in beta diversity between cases and controls (Bray–Curtis: p = 9.99 × 10−4; Jaccard: p = 9.99 × 10−4). The Shannon index showed a beneficial effect (OR = 0.59 (95%-CI (0.40, 0.87); p = 8 × 10−3). Cases were clearly discriminated from healthy controls by environmental information processing, signal transduction, two component system and membrane transport as significantly different functional pathways. Conclusions: In conclusion, our data indicate that an overall healthy lifestyle, in contrast to supplementation of single micro- or macronutrients, is most likely to reduce overall neurological abnormality risk and that the gut microbiome is an interesting target to develop novel preventive strategies.